The Millennium Development Goals for Health : Rising to the Challenges - Wagstaff, Adam (Washington, DC: World Bank, 2013)
The extent of premature death and ill health in the developing world is staggering. In 2000 almost 11 million children died before their fifth birthday, an estimated 140 million children under five are underweight, 3 million died from HIV/AIDS, tuberculosis claimed another 2 million lives, and 515,000 women died during pregnancy or child birth in 1995, almost all of them in the developing world. Death and ill health on such a scale are matters of concern in their own right. They are also a brake on economic development. These concerns led the international community to put health at the center of the Millennium Development Goals when adopting them at the Millennium Summit in September 2000. This report focuses on the health and nutrition Millennium Development Goals agreed to by over 180 governments. It assesses progress to date and prospects of achieving the goals. The report identifies what developing country governments can do to accelerate the pace of progress while ensuring that benefits accrue to the poorest and most disadvantaged households. It also pulls together the lessons of development assistance and country initiatives and innovations to improve the effectiveness of aid, based on a number of country case studies. It highlights some of the principles of effective development assistance: country driven coordination; strategic coherence expressed in comprehensive poverty reduction strategies, which fully address the issues of health, nutrition, and population; financial coherence embodied in medium term expenditure framework; pooling of donor funds; and a common framework for reporting and assessing progress.